Cooking dependent loss of metabolites in potato breeding lines and their wild and landrace relatives - Drapal, Margit; Lindqvist-Kreuze, H.; Mihovilovich, E.; Aponte, M.; Bonierbale, Merideth W.; Fraser, Paul D. (Elsevier, 2020)
Elucidating and improving the nutritional value of staple crops is an important focus in breeding programs. Hence, wild and cultivated potatoes have been metabolite profiled to assess metabolic plasticity present in potato tubers and changes that occur in these after cooking. The present data highlighted metabolic similarities of certain wild species to breeding lines, indicating preference during domestication. In the case of potato, the cooking process has to be taken into consideration for the assessment of nutritional quality. The degree of nutritional change during cooking depends on several factors including cooking method, stability of metabolites with nutritional properties and chemotype of the varietal matrix. The differences between raw and boiled tubers were similar within each germplasm group. No notable distinctions of total phenolic levels could be observed within germplasm groups, whereas total carotenoids and glycoalkaloids were significantly decreased. Genotypes/cultivars with notable changes upon cooking distinguished them within their genotype group.